Determinants of Growth Aspirations: Empirical Evidence of the South-Eastern European Countries - Karin Sirec; Dijana Mocnik (Economic Review: Journal of Economics and Business, 2013)
The purpose of the paper is to explore the growth aspirations of south-eastern European (SEE) countries (Bosnia and Herzegovina, Croatia, Greece, Hungary, Macedonia, Montenegro, Romania and Slovenia) early-stage entrepreneurs, concentrating on the relationship between a firm's innovative and international orientation and its growth aspirations. Innovative orientation and international orientation are referred as the most important dimensions of the growth aspirations and can be used for strengthening of a firm from SEE countries. We used firm's aspirations about the future employment as the operational measure of entrepreneurial growth. The data for our analysis is obtained from the 2010 Global Entrepreneurship Monitor Adult Population Survey (APS) in which 1,106 early-stage entrepreneurs from eight countries were identified. The results of the binary logistic regression show that innovative orientation is negatively related to the firms' growth aspirations. This means that the adoption of new technology as well as offering new products/services weakens the growth aspirations of the early-stage entrepreneurial SEE countries firms. The predictor of international orientation, too, is negatively and significantly associated with the growth aspirations. This means that internalisation impedes SEE countries firms' growth aspirations. The results also show that firms from innovation-driven countries have less negative growth aspirations compared to those from efficiency-driven countries.
Keywords: M13; L25; L26; 330; growth aspirations of early-stage enterpreneurs; Global Entrepreneurship Monitor; south-eastern European countries